2022
DOI: 10.1002/brb3.2741
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic lateral sclerosis and retinal changes in optical coherence tomography: A systematic review and meta‐analysis

Abstract: Introduction Increasing evidence suggests Amyotrophic Lateral Sclerosis (ALS) as a widespread pathological process comprising nonmotor features like fatigue, mild sensory symptoms, cognitive decline, and visual impairment. Measurements of retinal nerve fiber layer (RNFL) thickness using Optical Coherence Tomography (OCT) may correlate with the neurodegeneration associated with ALS. In addition to RNFL thickness, other OCT parameters have been explored in the context of diagnosing ALS and predicting disease sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…As evidenced, in MS and AD, the thinning of certain layers of the retina presents around the optic disc and in the macula. However, these findings are not specific to these diseases as they also occur in other neurological pathologies [17,18]. It is therefore of value to acquire new insight regarding the possible differences between the two diseases.…”
Section: Introductionmentioning
confidence: 96%
“…As evidenced, in MS and AD, the thinning of certain layers of the retina presents around the optic disc and in the macula. However, these findings are not specific to these diseases as they also occur in other neurological pathologies [17,18]. It is therefore of value to acquire new insight regarding the possible differences between the two diseases.…”
Section: Introductionmentioning
confidence: 96%
“… 4 Recent findings suggest that both ALS and PD can affect nonmotor components of the central nervous system, including cognitive impairment and optic nerve involvement. 5 6 7 …”
Section: Introductionmentioning
confidence: 99%
“… 11 Several studies employing OCT for retinal imaging in ALS patients have produced mostly cross-sectional data and variable conclusions. 6 7 12 …”
Section: Introductionmentioning
confidence: 99%
“…OCTA not only allows qualitative analysis of vascular lesions in various tomographies and regions but also provides quantitative analysis of blood flow density ( Xu et al, 2022 ). Numerous studies have indicated that OCTA can be employed for both the diagnosis and assessment of ophthalmological conditions including diabetic retinopathy, glaucoma, retinal vein occlusion, age-related macular degeneration, and ischemic optic neuropathy, as well as for investigating neurological diseases such as Alzheimer’s and demyelinating disorders ( Katsimpris et al, 2022 ; Nepal et al, 2022 ; Mohammadi et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%